Educational attainment is associated with unconditional helping behaviour. (11th December 2019) - Westlake, Grace; Coall, David; Grueter, Cyril C.
Abstract: Abstract: Altruism is a universal human trait, but little is known about its within-population variation. Socio-economic status (SES) has been found to positively impact altruism, but the specific socio-economic variables behind this relationship have remained elusive. This study aimed to determine which facets of SES predict altruism using a lost letter paradigm and a novel lost letter method. Six hundred letters (half dropped on the pavement, half sent to residential addresses) were distributed in 20 suburbs of Perth (Australia) differing in socio-economic variables. Letters distributed in high-SES neighbourhoods were more likely to be returned than letters distributed in low-SES neighbourhoods. Educational attainment and occupation status were the specific socio-economic variables underlying this association, while economic resources and crime rate were not associated with the likelihood of a letter being returned. These results suggest that altruism blossoms in neighbourhoods that are populated with highly educated individuals working in high-status jobs. The relationship between education and prosocial inclinations may be mediated by cognitive ability, self-control and high levels of socialization. Having experienced sustained exposure to norm-abiding models, more educated people may also be better at internalizing cultural norms of helping behaviour, thus creating a more altruistic environment where they reside.